(untitled) (Asian Journal of Agriculture, 2017)
Abstract. Suripto, Sukiman, Gunawan ER. 2017. Insecticidal selectivity of jayanti plant (Sesbania sesban) for integrated control of diamondback moth (Plutella xylostella). Asian J Agric 1: 80-84. It has been known previously that leaves of the jayanti plant (Sesbania sesban (L.) Merr.) contain insecticidal ingredients. This study aimed to evaluate the insecticidal selectivity of various extract fractions of S. sesban leaf for the integrated control of cabbage pest, the diamondback moths (Plutella xylostella). Dried leaf powders from S. sesban were extracted in stages by using hexane, dichloromethane (DCM), ethanol, and water, successively. Each insecticidal performance of S. sesban leaf extract fractions were tested against two types of test insects, namely P. xylostella larvae as target and Diadegma semiclausum imago as non-target insects according to completely randomized design in the cabbage plantation at the village of Sembalun, East Lombok, Indonesia. Each mortality data of P. xylostella larvae and D. semiclausum imago was processed by probit analysis to determine the concentration of the death of 50% of test insects (LC50) of each test extract. The results showed that the LC50 of S. sesban leaf extracts classified into four fractions, namely hexane, DCM, and water extract fractions to P. xylostella larvae successively was 343.71, 294.78, 29.95, and 1197.13 ppm, and to D. semiclausum imago row was 305.5, 121.56, 37.38, and 1043.70 ppm. The results showed that the insecticidal activity of S. sesban leaf ethanol extract fraction was selective because its selectivity value is 1.25. On the other hand, each insecticidal performance of three S. sesban leaf extracts, i.e., hexane, DCM, and water extract fractions, respectively is not selective, with the selectivity values are 0.89, 0.41, and 0.87.